ONE BLOCK, MANY USES. - Wilson, Rob (Architects' Journal, 2024)
Caruso St John's St Pancras Campus in London is a mixed-use development occupying a city block, featuring office, residential, light industrial, and retail spaces. The project aims to revitalize a neglected area, maintaining a balance of diverse uses and engaging with the local community. The architectural design combines European influences with modern elements, creating a cohesive urban environment that respects the historic fabric of the neighborhood.